The short story - Cox, Ailsa (Cambridge Scholars, 2008)
Long regarded as an undervalued and marginalised genre, the short story is undergoing a renaissance. The Short Story celebrates its unique appeal. Practitioners and scholars address the issues facing short story criticism in the 21st century. Author A.L.